Numerical investigation of stiffened plate girders under multiple patch loading - Ali, Mubashir; Rajeevan, B. (Journal of Structural Engineering, 2024)
Plate girders are widely used in long-span applications. Patch loading is one of the most typical loads a plate girder is subjected to. These partially distributed loads traverse along the span of a plate girder’s top or bottom flange. Length and number of patch loads are the governing factors that decide the system’s patch load capacity. The present study conducted a numerical investigation using finite element models developed in ABAQUS®. The existing experimental results in the literature were used to develop the numerical models and then validated against the results obtained from experiments. The effect of plate girders subjected to multiple patch loading was also evaluated and compared in this study. The spacing of patch loads allows for the distribution of the load to a larger area and influences the patch load capacity. The effect of multiple patch loads on longitudinally stiffened and unstiffened girders was evaluated. The optimum position of longitudinal stiffeners was found for girders subjected to multiple patch loading. The effect of different stiffener arrangements was assessed to find the most effective arrangement for efficiently resisting patch loads. Stiffeners placed close to the loaded flange were found beneficial in patch load resistance.